Creativity as the key to success—a plea for more guts in social marketing communication - Answin Vilmar (International Review on Public and Nonprofit Marketing, 2023)
Despite numerous campaigns, the efforts made not only to inform people of the Strategic Development Goals (SDGs) but also to persuade them to contribute individually to the task of achieving these goals have not yet been sufficient. Namely, awareness of the SDGs remains very low among broad sections of the population. In addition, the statements of these goals are not understood in many cases (World Economic Forum 10 ). Finally, behavioural changes based on relevant insights have hitherto been insufficient. This situation is also reflected in the UN report, which attests to the insufficient progress made with regard to achieving the SDGs in most countries and notes that in 2020 and 2021, the SDG Index Score even stagnated (Sachs et al., 6 ). However, when one's back is literally against the wall and the achievement of the SDGs within the establish timeframe seems to be becoming increasingly unlikely, the promotion of the courage necessary to find new creative solutions can represent an escape from this perceived standstill.
Keywords: 380; SDGs; Creativity; Communication; Campaign efficiency; WARC Creative 100